Developing learning resource centers in the light of the Saudi Kingdom vision 2030 - Al- Harbi, Haifa Ahmed (Journal of Educational and Psychological Sciences, 2019)
The aim of the this research is to uncover the reality of the learning resource centers in Saudi Arabia and the extent of their effectiveness in performing the role entrusted to them and to present a proposed vision to develop them in light of the vision of the Kingdom 2030. The researcher followed the descriptive descriptive approach to reach the reality of the learning resource centers in the Kingdom, identified the strengths, opportunities, and challenges of the current and future. The study revealed the importance of the Learning Resource Center in the process of teaching and learning and achieving the vision of the the Ministry of Education that has supported the learning resource centers with the equipment which helped to provide the services of the center at a good level, but to the present, it requires more support in terms of furniture and equipment, providing Internet service and updating digital and non- digital resources so as to increase the efficiency of work. Finaly, the researcher presented a number of recommendations and suggestions for the development of learning resource centers in light of the vision of the Kingdom 2030.